NKX6.1 transcription factor: a crucial regulator of pancreatic β cell development, identity, and proliferation - Idil I. Aigha (14913774) (2020)
Understanding the biology underlying the mechanisms and pathways regulating pancreatic β cell development is necessary to understand the pathology of diabetes mellitus (DM), which is characterized by the progressive reduction in insulin-producing β cell mass. Pluripotent stem cells (PSCs) can potentially offer an unlimited supply of functional β cells for cellular therapy and disease modeling of DM. Homeobox protein NKX6.1 is a transcription factor (TF) that plays a critical role in pancreatic β cell function and proliferation. In human pancreatic islet, NKX6.1 expression is exclusive to β cells and is undetectable in other islet cells. Several reports showed that activation of NKX6.1 in PSC-derived pancreatic progenitors (MPCs), expressing PDX1 (PDX1+/NKX6.1+), warrants their future commitment to monohormonal β cells. However, further differentiation of MPCs lacking NKX6.1 expression (PDX1+/NKX6.1−) results in an undesirable generation of non-functional polyhormonal β cells. The importance of NKX6.1 as a crucial regulator in MPC specification into functional β cells directs attentions to further investigating its mechanism and enhancing NKX6.1 expression as a means to increase β cell function and mass. Here, we shed light on the role of NKX6.1 during pancreatic β cell development and in directing the MPCs to functional monohormonal lineage. Furthermore, we address the transcriptional mechanisms and targets of NKX6.1 as well as its association with diabetes. Other Information Published in: Stem Cell Research & Therapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s13287-020-01977-0